Institutional environment for reproduction of social inequality - Dmytrenko, O. V.; Demchenko , S. A. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2018)
The article considers the institutional environment of the reproduction of social inequality on the basis of overseas and domestic studies. The institutional conditions for reducing social inequality in the transformational economy were analyzed. The role of social institutions in the formation of the present state of social inequality was studied. Therefore, socio-economic studies nowadays tend to focus on the institutional components of social inequality in different countries. The concept of social stratification is subject to a new interpretation, taking into account the factors of the institutional arrangement to reflect the stratification processes. The main attention was paid to determining the impact of social institutions on the formation and reproduction of social inequality. Therefore, comparative analyses were conducted which were largely focused on the study of the relationship of social inequality and the factors of the institutional environment. Thus, there was determined a list of institutional relations that can establish the basic parameters of social inequality in the society, and also characterize the differences in depth and dynamics of inequality in different economically developed countries. One of the suggested hypotheses is the power resource theory stating that the reduction of the role of institutional capital-intensive (power and property) of actors is possible only under the condition of employees’ heavily influence. The “median voter” hypothesis gained popularity in the countries with a proportional electoral system. It suggests that greater inequality in market distribution of revenues will lead to an increase in the levels of redistribution by the state in the event of inequality growth. When studying institutional factors of social inequality considerable attention was paid to such a social institution as professional unions. Trade unions are powerful participants in salary distribution, guarantors of social benefits, and are able to effectively influence employees. The institute of education performs socializing and educational functions. It also acts as one of the main channels of communication between a stratified system of social positions and individuals of different social backgrounds and abilities. When analysizing the functioning of the institute of education, the focus is made on availability of all levels of education for children of different social backgrounds, as well as their success in learning.